Regional hydrological impacts of climatic change : hydroclimatic variability : part 2 of the proceedings of the International Symposium on Regional Hodrological Impacts of Climatic Variability and Change with an Emphasis on Less Developed Countries (S6) held during the Seventh Scientific Assembly of the International Association of Hydrological Sciences (IAHS) at Foz do Iguaço, Brazil, 3 - 9 April 2005 - Franks, Stewart (IAHS Publication, 2005)
Druhá část příspěvků z Mezinárodního symposia o dopadech klimatických změn na regionální hydrologii s důrazem na méně rozvinuté země, konaného během 7. vědeckého setkání Mezinárodní asociace hydrologie (IAHS) v Brazílii ve dnech 3.-9. dubna 2005. Sborník obsahuje 31 článků zabývajících se hydroklimatickou variabilitou, rozdělených podle geografických regionů (Jižní Amerika, Oceánie, Severní Amerika a Evropa, Afrika, Asie).